Book Review: Surviving Debt Expert Advice for Getting Out of Financial Trouble - Audrey Kernodle (Journal of Financial Therapy, 2020)
Surviving Debt: Expert Advice for Getting Out of Financial Trouble is a comprehensive synthesis of techniques and advice from the nation’s consumer law experts that provides all the fundamental information needed to manage debt in the United States.